The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/10283153211016266
|View full text |Cite
|
Sign up to set email alerts
|

Transitions Across Multi-Worlds: Experiences of Chinese International Doctoral Students in STEM Fields

Abstract: In the context of internationalization, this longitudinal qualitative study explores the diverse and challenging experiences of Chinese international doctoral students in science, technology, engineering, and mathematics. The endeavor is to identify factors that facilitate or constrain their successful completion of a PhD abroad over time. By incorporating a three-dimensional multi-world conceptual framework that highlights the relationship between an individual’s research, personal, and social worlds, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 200 publications
(437 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, and although a growing body of research focuses on IDS and on challenges and difficulties faced in their doctoral experiences (e.g., Doyle et al, 2017; Hu et al, 2016; Laufer and Gorup, 2019; Pinto, 2021; Winchester-Seeto et al, 2014; Yang and MacCallum, 2021), research dealing specifically with the qualities for supervising IDS is scarce, and in Portugal, it is inexistent. The general qualities and competences put forward in the literature seem adequate to supervising IDS, but as highlighted by Adrian-Taylor et al (2007), supervisors are central figures in IDS’ journeys since these ‘tend to have fewer social supports to help them cope with the many challenges they face while studying abroad’ (p. 92).…”
Section: Doctoral Supervision: Supervisors’ Qualitiesmentioning
confidence: 99%
“…Nevertheless, and although a growing body of research focuses on IDS and on challenges and difficulties faced in their doctoral experiences (e.g., Doyle et al, 2017; Hu et al, 2016; Laufer and Gorup, 2019; Pinto, 2021; Winchester-Seeto et al, 2014; Yang and MacCallum, 2021), research dealing specifically with the qualities for supervising IDS is scarce, and in Portugal, it is inexistent. The general qualities and competences put forward in the literature seem adequate to supervising IDS, but as highlighted by Adrian-Taylor et al (2007), supervisors are central figures in IDS’ journeys since these ‘tend to have fewer social supports to help them cope with the many challenges they face while studying abroad’ (p. 92).…”
Section: Doctoral Supervision: Supervisors’ Qualitiesmentioning
confidence: 99%
“…Mwangi, Changamire, and Mosselson found that financial concerns were a major issue for participants in their study, creating stress and distractions from academic work [23]. Lastly, Yang and MacCallum note that financial challenges, such as a shortage of funding, are a reality for international graduate students, but with support and understanding, these students can adapt and achieve despite these difficulties [25].…”
Section: Literature Review a What Do Graduate International Students ...mentioning
confidence: 98%
“…Moreover, these students often describe a lack of ethnic diversity and a predominant whiteness on their campuses, which can be hugely different from their countries of origin [23]. In addition, the classroom presents various challenges, including participation expectations, discussions that center the US context, limited space for multicultural perspectives, and conflicting worldviews [23], [25]. However, Yang and MacCallum found that despite the challenges and difficulties international graduate students face, with multilateral and reciprocal understanding, accommodation, and respect for differences, they were able to adapt and be successful [25].…”
Section: Literature Review a What Do Graduate International Students ...mentioning
confidence: 99%
See 1 more Smart Citation